Kebebasan Beragama di Indonesia dalam Perspektif Hak Asasi Manusia - Robert Mirsel (Jurnal Ledalero, 2022)
Freedom of religion and belief has long been accepted globally as human rights. This right is formally enshrined in international human rights instruments such as the Universal Declaration of Human Rights and the International Covenant on Civil and Political Rights. Indonesia has also adopted these international human rights instruments in its policies and implementation in the applicable laws as seen in the inclusion of this right in the 1945 Constitution, Law no. 39 of 1999 and Law no. 12 of 2005. However, in practice, this right is often violated by the state and civil society either by action (commission) or by omission.  This study also shows religious intolerance, radicalism, and fundamentalism are the manifestations of real challenges in promoting unity in diversity in the country. Therefore, this study recommends the Indonesian government to: review some its policies that are contrary to international and national human rights instruments; cancel lower legal products that are contrary to the 1945 Constitution and other laws; take legal action to suppress and prevent radical and intolerant groups from carrying out violence, discrimination and persecution against certain religious minorities; restore the rights of groups or individuals that have been violated in relation to the freedom to practice or adhere to their respective religions; and improve religious tolerance and moderation education in formal and non-formal educational institutions.Keywords: kebebasan beragama; hak asasi manusia; instrumen HAM; intoleransi; toleransi; kekerasan; moderasi beragama.